The Implementation of Zakat Distribution by BAZNAS of Jambi City - Putri Handayani, Novia; Addiarrahman; Hilmi (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2024)
Zakat, a pillar of Islam, serves as a crucial wealth distribution mechanism aimed at reducing socio-economic inequalities. With Indonesia`s vast Muslim population, the potential of zakat is significant, yet its impact relies heavily on effective management and distribution. This study explores the implementation of zakat distribution by BAZNAS of Jambi City, focusing on its processes, effectiveness, challenges, and proposed solutions. This research utilizes a qualitative case study approach, involving BAZNAS administrators, field officers, and zakat recipients (mustahik) to gain insights into the zakat distribution in Jambi City. The findings reveal that BAZNAS Jambi City has developed a structured zakat distribution system, encompassing mustahik data collection, verification, and fund allocation. The BAZNAS Jambi City categorizes zakat distribution into consumptive, productive, and special programs, each with specific targets. However, challenges such as limited human resources, budget constraints, and a lack of continuous assistance in productive zakat programs were identified, impacting the long-term benefits for mustahik. Despite these challenges, BAZNAS Jambi City has made efforts to improve the distribution process, including the creation of Zakat Collection Units and seeking the issuance of local regulations to ensure consistent zakat collection. The study concludes that while BAZNAS Jambi City`s zakat distribution has made strides in improving community welfare, there is a need for enhanced mentoring and innovation to maximize the impact of productive zakat programs. The research provides valuable recommendations for BAZNAS and other regions to refine their zakat distribution strategies, ultimately contributing to poverty alleviation and economic empowerment.